A comparative study of the outcome of displaced fractures neck of femur treated with unipolar prosthesis and fenestrated bipolar prosthesis in active elderly patients - Aminul Islam, Mohammad; Debnath, Shaymal Chandra; Hossen, Muhammad Anwar; Shahnewas (International Journal of Research in Orthopaedics, 2023)
Background: Fractures of the neck or femur are among the most serious surgical problems affecting older groups. These fractures constitute a large burden on families and society due to the inability to stand and walk. Objectives were to compare the functional outcomes of unipolar (Austin-Moore) versus uncemented bipolar hemiarthroplasty in displaced fractures neck femur among these active elderly patients. Methods: This prospective interventional study was carried out at NITOR, Dhaka, Bangladesh in total 60 patients. Among them, 30 patients were treated with unipolar and 30 patients were treated with fenestrated bipolar prosthesis through a lateral approach. Results: There was no significant age difference between the two groups. Regarding the functional outcome, 6 (20%) patients in the unipolar group and 11 (36.67%) patients in the bipolar group had excellent outcomes. About the same number of patients had good outcomes 36.67% in the unipolar and 43.33% in the bipolar group; the fair and poor outcome was more in the unipolar group than the bipolar group. So, the final outcome after 6 months of operation, 57.57% of patients had satisfactory results in the unipolar group whereas 80% of patients had satisfactory results in the bipolar group. The average Harris hip score was 77.14±14.58 in the unipolar group and 84.63±10.15 in the bipolar group and the p=0.01 which is below 0.05. So, the result is statistically significant. Conclusions: Uncemented bipolar hemiarthroplasty with a fenestrated stem can give better functional outcomes for displaced intracapsular femoral neck fractures in active elderly patients compared to Austin-Moore prostheses.